2002
DOI: 10.1021/om020654b
|View full text |Cite
|
Sign up to set email alerts
|

Organometallic Compounds of the Lanthanides. 158.1 Alkenyl-Functionalized Cyclopentadienyl Complexes of Yttrium, Samarium, and Lutetium and Their Hydroboration

Abstract: YCl 3 , SmCl 3 , and LuCl 3 react with (tetramethylvinylcyclopentadienyl)lithium (1a), yielding (CH 2 dCHC 5 Me 4 ) 2 Ln(µ-Cl) 2 Li(Et 2 O) 2 (Ln ) Y (2a), Sm (2b), Lu (2c)). LuCl 3 and the analogous potassium salt 1b form oligomeric [(CH 2 dCHC 5 Me 4 ) 2 Lu(µ 3 -Cl) 2 K(THF)] n (3). Methylation of the yttrium complex 2a with MeLi gives (CH 2 dCHC 5 Me 4 ) 2 Y(µ-CH 3 ) 2 Li(THF) (4). Hydroboration of the complexes 2a-c with 9-BBN results in the formation of (C 8 H 14 BCH 2 -CH 2 C 5 Me 4 ) 2 Ln(µ-Cl) 2 Li(THF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
14
0
1

Year Published

2004
2004
2009
2009

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(16 citation statements)
references
References 45 publications
1
14
0
1
Order By: Relevance
“…The dialkyl complexes ½MðRÞCHðg 5 -C 5 Me 4 Þðg 5 -C 5 H 4 ÞR 0 2 ] [M = Ti, R = CH 2 =CHCH 2 , R 0 = Me (6), R 0 = CH 2 Ph (7); R = CH 2 C(CH 3 )@CH 2 , R 0 = Me (8), R 0 = CH 2 Ph (9); M = Zr, R = CH 2 CH@CH 2 , R 0 = Me (10), R 0 = CH 2 Ph (11); R = CH 2 C(CH 3 )@CH 2 , R 0 = Me (12), R 0 = CH 2 Ph (13)] have been synthesized by the reaction of the corresponding ansa-metallocene dichloride complexes 2-5 and two molar equivalents of the alkyl Grignard reagent. Compounds 2-5 reacted with H 2 under catalytic conditions (Wilkinson's catalyst or Pd/C) to give the hydrogenation products [M{(R)CH(g 5 -C 5 Me 4 )(g 5 -C 5 H 4 )}Cl 2 ] [M = Ti and R = CH 2 CH 2 CH 3 (14) or R = CH 2 CH(CH 3 ) 2 (15); M = Zr and R = CH 2 CH 2 CH 3 (16) or R = CH 2 CH(CH 3 ) 2 (17)]. The reactivity of 2-5 has also been tested in hydroboration and hydrosilylation reactions.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The dialkyl complexes ½MðRÞCHðg 5 -C 5 Me 4 Þðg 5 -C 5 H 4 ÞR 0 2 ] [M = Ti, R = CH 2 =CHCH 2 , R 0 = Me (6), R 0 = CH 2 Ph (7); R = CH 2 C(CH 3 )@CH 2 , R 0 = Me (8), R 0 = CH 2 Ph (9); M = Zr, R = CH 2 CH@CH 2 , R 0 = Me (10), R 0 = CH 2 Ph (11); R = CH 2 C(CH 3 )@CH 2 , R 0 = Me (12), R 0 = CH 2 Ph (13)] have been synthesized by the reaction of the corresponding ansa-metallocene dichloride complexes 2-5 and two molar equivalents of the alkyl Grignard reagent. Compounds 2-5 reacted with H 2 under catalytic conditions (Wilkinson's catalyst or Pd/C) to give the hydrogenation products [M{(R)CH(g 5 -C 5 Me 4 )(g 5 -C 5 H 4 )}Cl 2 ] [M = Ti and R = CH 2 CH 2 CH 3 (14) or R = CH 2 CH(CH 3 ) 2 (15); M = Zr and R = CH 2 CH 2 CH 3 (16) or R = CH 2 CH(CH 3 ) 2 (17)]. The reactivity of 2-5 has also been tested in hydroboration and hydrosilylation reactions.…”
mentioning
confidence: 99%
“…Hydroboration at the double bond of the allyl group of the ansametallocene complexes 2-5 was carried out in a similar manner to that published by our group [11d,f] or Erker, Piers or Alt for metallocene complexes of group 4 [14] or Schumann for lantanocene complexes [15]. 9-BBN was used as the reagent with complexes 2-5 to give mainly anti-Markonikov products [M{(9-BBN-CH 2 CH(R)CH 2 )CH(g 5 -C 5 Me 4 )(g 5 -C 5 H 4 )}Cl 2 ] [M = Ti and R = H (18); M = Zr and R = H (19) or R = CH 3 (20)] (Scheme 5).…”
mentioning
confidence: 99%
“…The six Y-C1 bonds involved in the formation of Y-Cl-Y bridges display distances in the range 2.677(1)-2.860(1) Å (2.77 Å on average), and are slightly longer than those observed in dimeric bis[(µ-Cl)Y III (cyclopentadienyl)] complexes (2.66-2.70 Å). [11][12][13] This Y-Cl lengthening can be justified by the presence of a µ-Cl bridge between yttrium atoms and two µ 3 -Cl bridges which involve all three metal centers. The remaining µ-Cl1 and µ-Cl5 chlorides connecting yttrium atoms with lithium display shorter Y-Cl distances of 2.607(2) and 2.627(1) Å, in agreement with those found in the range 2.62-2.65 Å in similar Y-Cl-Li fragments.…”
Section: Crystal Structuresmentioning
confidence: 99%
“…[24] We also noticed some differences between the polymers obtained with the methylsubstituted (7) and phenyl-substituted (11) derivatives. While with the methyl-substituted complex 7, after the usual work-up, a single fraction of highly linear polyethylene was produced (single peak at δ = 27.7 ppm in the 13 C NMR spectrum), with the phenyl-substituted complex 11 the yield was almost twice as high but the solid consisted of two fractions, the first (43 %) of which is similar to the polymer isolated with the catalyst 7 and the second (57 %) of which contains a mixture of oligomers. Apparently this different behavior can be attributed to the influence of the substituent in the ancillary ligand.…”
Section: Polymerization Studiesmentioning
confidence: 99%
“…It has been found that organolanthanide complexes behaves a diverse chemistry including catalytic transformations of olefins and lactones polymerization [2], hydroamination/cyclization [3], hydrosilylation [4], hydrophosphination [3b,5], and hydroboration [6]. Organolanthanide(II) complexes are one of the family among the organolanthanide complexes, which can effect various reactions including activation of small molecules such as N 2 [7], CO [8], unsaturated hydrocarbons [9], carbonyl [10], as well as polymerization of ethylene [2], styrene [2], acrylonitrile [11], methyl methacrylate and lactones [2,12].…”
Section: Introductionmentioning
confidence: 99%